A critical analysis of Prophetic narrations mentioned in KAFA JAKIM's ibadah (Worship) textbooks - Muhamad Rozaimi Ramle (2020)
Recent statistic shows that 525,832 children are registered as KAFA students in Malaysia. This proves that KAFA School under the supervision of JAKIM has gained the trust of Muslim parents to send their children to learn about Islam in their early childhood. However, a large number of them are also at risk of obtaining inaccurate information about Islam if the sources of references do not provide the authentic information about Islam. The purpose of this study is to identify the authenticity of the Prophetic traditions (had?ths) that are referred to in the KAFA Worship Textbook used by the students. This study is a qualitative study using the method of takhrij of had?th (had?th verification) in which the had?ths are examined and evaluated for their validity based on the comments of the scholars on its chain of narrators and its texts. This study analyzed three had?ths used in the entire textbook of worship subjects and one of them was found to be a weak narration. This study recommends that all had?ths referenced in the school textbooks should be evaluated and approved by a panel of had?th experts before they can be used as references for students and teachers.